Digital Innovation and Knowledge Management: The Latest Approaches in International Business. A Systematic Literature Review in the Indonesian Context. - Zaenal Aripin; Nida Garnida Fitrianti; Raden Roro Fatmasari (Yayasan Kreatif Indonesia Emas, 2023)
In an era of increasingly digitally connected globalization, innovation and knowledge management play a crucial role in shaping the international business landscape. This study conducts a systematic literature review to explore the latest approaches in digital innovation and knowledge management, particularly in the context of international business in Indonesia. The analysis outlines the evolution of the concepts of digital innovation and knowledge management, identifies key trends, and evaluates their impact on global business strategies. The study provides in-depth insights into how companies can adopt and optimize digital innovation as well as leverage knowledge management to improve competitiveness in the global marketplace. The findings of this study are expected to provide guidance for business practitioners, academics, and policymakers in designing knowledge-based strategies to support international business growth in the digital era.